Comparative Study of Point Intercept Transect (PIT) Method and Underwater Photo Transect (UPT) to Calculate Hard Coral Cover Percentage - Johan Danu Prasetya; Dian Hudawan Santoso (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • Point Intercept Transect Method (PIT) and Underwater Photo Transect (UPT) to monitor coral cover was compared • Percentage of hard coral cover was analyzed • The average difference of the percentage of hard coral cover obtained from the PIT and UPT was analyzed